P0125 A phase 1/2 trial of BNC105P with everolimus in metastatic renal cell carcinoma. (July 2015) - Pal, S.; Azad, A.; Bhatia, S.; Drabkin, H.; Costello, B.; Sarantopoulos, J.; Kanesvaran, R.; Lauer, R.; Sweeney, C.; Hahn, N.; Sonpavde, G.; Richey, S.; et al.
Abstract : Background: In patients with metastatic renal cell carcinoma (mRCC), everolimus represents a standard of care option for patients who have had prior vascular endothelial growth factor (VEGF)-directed therapy. BNC105P is an inhibitor of tubulin polymerisation and preclinical studies suggest possible synergy with everolimus. In this phase 1/2 study, the efficacy and safety of the combination was explored. Methods: A phase 1 study in patients with clear-cell mRCC and any number of different prior treatments was done using a classical 3+3 design to evaluate standard doses of everolimus with increasing doses of BNC105P (4.2, 8.4, 12.6, and 16 mg/m 2 ). At the recommended phase 2 dose, patients with clear-cell mRCC and one to two prior treatments (including ⩾1 VEGF-TKI) were randomised to BNC105P with everolimus (group A) or everolimus alone (group B). Patients were stratified by MSKCC risk factors and number of prior VEGF-TKIs. The primary endpoint of the study was 6-month progression-free survival. Findings: 15 patients were included in the phase 1 component, and a dose of BNC105P at 16 mg/m 2 with everolimus at 10 mg daily was identified as the recommended phase 2 dose. In the phase 2 study, 139 patients were randomised across 77 treatment centres (United States of America (USA): 63; non-USA: 14), with 69 and 67 evaluable patients in groups A and B, respectively. Six-month progression-free survival was similar in the treatment groups (group A: 33.82% versus group B: 30.30%, p  = 0.66) and no difference in median progression-free survival was observed (group A: 4.7 months versus group B: 4.1 months; p  = 0.49). Most adverse events were consistent with everolimus-related toxic effects. Changes in several biomarkers (matrix metalloproteinase-9, stem-cell factor, sex hormone binding globulin, and serum amyloid A protein) were associated with clinical outcome with BNC105P. Conclusions: Although the primary endpoint was not met in an unselected population, intriguing correlative studies suggest several potentially predictive biomarkers. Further prospective assessment of BNC105P in relevant biomarker-based subsets is warranted.